The bell curve intelligence and class structure in American life - Herrnstein, Richard J.; Murray, Charles A. (New York The Free Press, 1994)
Breaking new ground and old taboos, Richard J. Herrnstein and Charles Murray tell the story of a society in transformation. At the top, a cognitive elite is forming in which the passkey to the best schools and the best jobs is no longer social background but high intelligence. At the bottom, the common denominator of the underclass is increasingly low intelligence rather than racial or social disadvantage. The Bell Curve describes the state of scientific knowledge about questions that have been on people's minds for years but have been considered too sensitive to talk about openly -- among them, IQ's relationship to crime, unemployment, welfare, child neglect, poverty, and illegitimacy; ethnic differences in intelligence; trends in fertility among women of different levels of intelligence; and what policy can do -- and cannot do -- to compensate for differences in intelligence. Brilliantly argued and meticulously documented, The Bell Curve is the essential first step in coming to grips with the nation's social problems.
Cognitive class and education, 1900-1990 --- Cognitive partitioning by occupation --- The economic pressure to partition --- Steeper ladders, narrower gates --- Poverty --- Schooling --- Unemployment, idleness, and injury --- Family matters --- Welfare dependency --- Parenting --- Crime --- Civility and citizenship --- Ethnic differences in cognitive ability --- Ethnic inequalities in relation to IQ --- The demography of intelligence --- Social behavior and the prevalence of low cognitive ability --- Raising cognitive ability --- The leveling of American education --- Affirmative action in higher education --- Affirmative action in the workplace --- The way we are headed --- A place for everyone.
Includes bibliographical references (pages 775-832) and index.
Keywords: Intellect; Nature and nurture; Intelligence levels -- Social aspects; Educational psychology